2018
DOI: 10.1007/s11894-018-0635-8
|View full text |Cite
|
Sign up to set email alerts
|

Update in the Care and Management of Patients with Primary Sclerosing Cholangitis

Abstract: Drugs under investigation include norursodeoxycholic acid, nuclear receptor agonists, anti-fibrotics, antibiotics, and anti-inflammatory drugs. Endoscopic therapy is indicated for symptomatic dominant strictures and in the work-up of malignancies. Recently, the use of stents was associated with an increased rate of complications compared to balloon dilatation; and long-term stenting should be avoided. Malignancies currently account for most of the PSC-related mortality. Many drugs are emerging for the treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 104 publications
0
7
0
Order By: Relevance
“…22,25 Despite the unclear long-term benefits of endoscopic therapy, multiple techniques for symptom relief in patients affected by PSC have been studied, particularly the endoscopic treatment of dominant strictures. 7,25 Studies comparing the endoscopic management of PSC-related dominant strictures are necessary, since such procedures carry the potential to alter the survival and prognosis of patients, although the duration of liver transplant-free survival associated with these interventions remains unclear. 23 Based on the results of this systematic review and meta-analysis of over 460 patients, stent placement for dominant strictures in PSC appeared to associate with higher complication rates without significant differences in efficacy when compared to balloon dilation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…22,25 Despite the unclear long-term benefits of endoscopic therapy, multiple techniques for symptom relief in patients affected by PSC have been studied, particularly the endoscopic treatment of dominant strictures. 7,25 Studies comparing the endoscopic management of PSC-related dominant strictures are necessary, since such procedures carry the potential to alter the survival and prognosis of patients, although the duration of liver transplant-free survival associated with these interventions remains unclear. 23 Based on the results of this systematic review and meta-analysis of over 460 patients, stent placement for dominant strictures in PSC appeared to associate with higher complication rates without significant differences in efficacy when compared to balloon dilation.…”
Section: Discussionmentioning
confidence: 99%
“…The presentation of PSC is highly variable, ranging from asymptomatic in the early stages, to recurrent episodes of cholangitis with fever, jaundice, pruritus, abdominal pain and fatigue. However, median survival tends to be significantly decreased in patients who are symptomatic at the time of diagnosis [ 6 , 7 ]. Epidemiological studies of PSC have reported a prevalence rate of approximately 1 per 10,000, and incidence rates between 0.4 and 2.0 per 100,000 per year in Northern Europe and the US [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Preliminary studies are starting to suggest the presence of a distinct intestinal microbiome in PSC patients characterized by an overabundance of potentially pathogenic bacteria [4]. Multiple studies have also demonstrated biochemical response in PSC patients treated with different antibiotics, suggesting that infection may play a role in the development of PSC [5]. All of this goes towards suggesting that an infectious etiology may underlie the pathogenesis of both PBC and PSC.…”
Section: Introductionmentioning
confidence: 99%